A rare case of extensive idiopathic scrotal calcinosis - Myreddy, Neeraja; Chaitanya, B; Bhavani, C; Swapna, R Sujeeva (International Journal of Medical Research and Review, 2014)
Idiopathic scrotal calcinosis (also known as “Idiopathic calcified nodules of the scrotum”) is a cutaneous condition characterized by the deposition of calcium and phosphorous salts on scrotal skin. It presents as solitary or multiple, typically asymptomatic, hard yellowish intradermal nodules. Its etiology and pathogenesis are still debated. We report a case of a 30 year old male patient affected by the same with review of literature.